RI 4541 Investigation Of Comet Coalition Lead-Zinc Deposit, Lincoln County, Nev. - Russell R. Trengove (The National Institute for Occupational Safety and Health (NIOSH), 1949)
In order to extend or delimit the known ore reserves adjacent to the Comet Coalition property on the western slope of the Highland Peak Range about 8 airline miles west of Pioche, Nev., the Bureau of Mines undertook an exploration project of diamond drilling. Production figures from this property, formerly known as the Schodde, are not available, but it has been reported that small amounts of rich silver and gold ore were Shipped by wagon to a smelter in the Salt Lake valley during 1900-1910. Small shipments were reported for the period 1915-1927, also. A study of the Pioche District by the Federal Geological Survey in 1942 and 1943 was the basis for the exploration program of the Bureau of Mines in 1947 This program consisted of diamond-drilling three holes. The total footage was 2,967 feet. No. 1 hole was drilled 1,260 feet, a record depth for diamond drilling in the Pioche District. Silver-bearing lead-zinc sulfide ores are found in the Combined Metals limestone, known locally as the C.M. bed, These deposits have been formed by replacement of the limestone that is inclosed in the Pioche shale.